Implementation of Generative Asset Platform Governance for Optimizing Social Media Branding Assets in the Pacitan Smart Community - Surya, Eka Putri; Roziqin, Mohamad Firzon Ainur; Ningrum, Linda Agustin; Iriaji, Iriaji; Marcelliantika, Adinda; Aruna, Alby; Wijaya, Ginanjar Atma (Abdimas Indonesian Journal, 2024)
The implementation of generative asset platform management for optimizing social media branding assets in the Pacitan Cerdas Community aims to enhance the effectiveness of branding strategies and community engagement on social media. This program integrates generative asset technology with good governance to produce consistent, engaging, and relevant social media content. Methods include technical training for community members, development and implementation of the generative asset platform, and performance evaluation through social media metrics analysis. The results show a significant increase in interaction and user engagement. The implementation of this management system is expected to support the development of a strong digital identity and expand the community's reach on social media.